Factors predicting the outcome of customised foot orthoses in patients with rheumatoid arthritis: a prospective cohort study - Roorda Leo D (Journal of Foot and Ankle Research, 2011)
Abstract Background Conservative management of foot problems in patients with rheumatoid arthritis (RA) may consist of the prescription of customised foot orthoses. Indications for foot orthoses are not clear and the effectiveness of the intervention is highly variable among patients. Knowledge on which patients benefit the most from foot orthoses can help to select patients eligible for this type of intervention. The objective of the present study was to determine clinical and demographic factors that predict the outcome of customised foot orthoses on pain and disability in patients with RA. Methods A total of 135 RA patients who were supplied with customised foot orthoses were included in this prospective cohort study. Pain and disability were measured before and after the intervention period using a Numeric Rating Scale (NRS) for foot pain, the Foot Function Index (FFI), the Western Ontario and McMasters Universities Osteoarthritis Index (WOMAC) and a 10-meter walking test. The intervention period consisted of one or more appointments with the podiatrist during which the foot orthoses were customised. Swollen foot joint count, foot deformity scores, forefoot peak pressure, disease duration, age, gender, body mass index and baseline values of the outcome measures were selected as potential factors predicting outcome. Multivariate linear regression analyses were performed to determine factors associated with change in pain and disability (at P < 0.05). Results Disease duration was negatively associated with the change scores in NRS foot pain (P = 0.018), WOMAC pain (P = 0.001), FFI disability (P = 0.003) and WOMAC physical function (P = 0.002). Age was negatively associated with the change score in 10 meter walking time (P = 0.008). For all outcome measures baseline values were positively associated with the change scores (P < 0.001). Conclusions Shorter disease duration predicted greater improvements in self-reported foot pain and disability, and younger age predicted greater improvements in walking time after intervention with foot orthoses. Also, higher baseline values of pain and disability predicted greater improvements. Referral for conservative management with foot orthoses in the early stage of RA seems important when aiming to achieve reduction in pain and improvement in daily activities.